Left Dislocation: a typological overview - Westbury, Josh (Stellenbosch Papers in Linguistics Plus, 2016)
The Left Dislocation construction is a typologically universal phenomenon that has received detailed analysis, from both formal and functional perspectives, in a number of genetically and areally diverse languages. The present paper aims to provide a general overview of this cross-linguistic research with a concentration on: 1) the comparison of syntactico-semantic features of LD across languages, 2) the generalized cross-linguistic patterns and categories attested for LD, and 3) the explanations offered for LD in terms of its motivation and function in discourse. Accordingly, the paper will proceed in two parts. The first part will entail a brief survey of the syntactic and semantic attributes that have established LD as a typological category. In light of these attributes, linguists generally distinguish between two broad types of LD on the basis of particular syntactic patterns and constraints. Thus, a general description of these types is provided, along with a brief description of several less prototypical LD types. The second part of the paper will focus on the explanation of LD both in terms of the cognitive and contextual constraints that motivate its use in discourse, as well as the communicative goals and pragmatic effects achieved by the construction in particular contexts.